A mitochondrial division inhibitor, Mdivi-1, inhibits mitochondrial fragmentation and attenuates kainic acid-induced hippocampal cell death. Issue 1 (December 2016) - Kim, Hwajin; Lee, Jong; Park, Keon; Kim, Won-Ho; Roh, Gu
Abstract Background Kainic acid (KA)-induced excitotoxicity promotes cytoplasmic calcium accumulation, oxidative stress, and apoptotic signaling, leading to hippocampal neuronal death. Mitochondria play a critical role in neuroinflammation and the oxidative stress response. Mitochondrial morphology is disrupted during KA-induced seizures; however, it is not clear whether mitochondrial fission or fusion factors are involved in KA-induced neuronal death. Results We investigated the effect of Mdivi-1, a chemical inhibitor of the mitochondrial fission protein Drp1, on mitochondrial morphology and function in KA-injected mice. Mdivi-1 pretreatment significantly reduced seizure activity and increased survival rates of KA-treated mice. Mdivi-1 was protective against mitochondrial morphological disruption, and it reduced levels of phosphorylated Drp1 (Ser616) and Parkin recruitment to mitochondria. By contrast, levels of mitochondrial fusion factors did not change. Mdivi-1 also reduced KA-induced neuroinflammation and glial activation. Conclusions We conclude that inhibition of mitochondrial fission attenuates Parkin-mediated mitochondrial degradation and protects from KA-induced hippocampal neuronal cell death.